Categorization of the Ocular Microbiome in Japanese Stevens–Johnson Syndrome Patients With Severe Ocular Complications - Ueta, Mayumi; Hosomi, Koji; Park, Jonguk; Mizuguchi, Kenji; Sotozono, Chie; Kinoshita, Shigeru; Kunisawa, Jun (Frontiers in Cellular and Infection Microbiology, 2021)
The commensal microbiota is involved in a variety of diseases. Our group has noticed that patients with Stevens–Johnson syndrome (SJS) / toxic epidermal necrolysis (TEN) often present with persistent inflammation of the ocular surface, even in the chronic stage, and that this inflammation is exacerbated by colonization of the mucosa by certain bacteria. However, the changes in the composition of the ocular microbiome in SJS/TEN with severe ocular complications (SOC) patients remains to be fully investigated. Here, we conducted a cross-sectional study of 46 Japanese subjects comprising 9 healthy control subjects and 37 SJS/TEN patients with SOC. 16S rRNA-based genetic analyses revealed that the diversity of the ocular microbiome was reduced in SJS/TEN patients with SOC compared with that in healthy control subjects. Principal coordinate analysis based on Bray–Curtis distance at the genus level revealed that the relative composition of the ocular microbiome was different in healthy control subjects and SJS/TEN patients with SOC, and that the SJS/TEN patients with SOC could be divided into four groups based on whether their microbiome was characterized by enrichment of species in genus Corynebacterium 1, Neisseriaceae uncultured, or Staphylococcus or by simultaneous enrichment in species in genera Propionibacterium, Streptococcus, Fusobacterium, Lawsonella, and Serratia. Collectively, our findings indicate that enrichment of certain bacteria at the ocular surface could be associated with ocular surface inflammation in SJS/TEN patients with SOC.